Composite electrolyte, lithium metal battery and application of lithium metal battery

By using a composite electrolyte of fluorinated ring ether and alkane solvent in lithium metal batteries, the chemical reaction is controlled to form a stable electrolyte, which solves the problems of side reactions and temperature sensitivity of lithium metal batteries, and achieves efficient and safe battery performance .

CN119230938APending Publication Date: 2024-12-31SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411501278.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Lithium metal batteries have high reaction activity and low redox potential, resulting in frequent side reactions, forming poor solid electrolytes, affecting efficiency and cycle life, and are sensitive to temperature, limiting their application at extreme temperatures.

Method used

Using a composite electrolyte, including fluorinated ring ether solvent, alkane solvent, LiPF6 and LiTFSI, the ring opening polymerization reaction of fluorinated ring ethers is initiated by controlling the number, volume ratio and molar concentration ratio of its backbone carbon atoms, and the ring opening polymerization reaction is formed to form a rich content. The solid electrolyte of inorganic LiF and highly elastic polyether inhibits side reactions and improves the stability of lithium ions.

Benefits of technology

The high Coulombic efficiency, excellent cycle performance, rate performance and safety performance of lithium metal batteries are achieved, especially in low temperature environments, the performance of the battery is significantly improved, the formation of solid electrolytes is avoided, and the life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102675190000111
    Figure BDA0005102675190000111
  • Figure BDA0005102675190000121
    Figure BDA0005102675190000121
  • Figure FDA0005102675170000021
    Figure FDA0005102675170000021
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite electrolyte, a lithium metal battery and application of the lithium metal battery. The invention relates to a composite electrolyte which comprises a fluorinated cyclic ether solvent, an alkane solvent, LiPF6 and LiTFSI, the carbon atom number Ra of the fluorinated cyclic ether solvent skeleton is more than or equal to 3 and less than or equal to 6; the volume ratio A of the fluorinated cyclic ether solvent is greater than or equal to 50% and smaller than or equal to Alt; 100%; the volume ratio B of the alkane solvent meets 0 lt; b < = 50%; the structural tortuosity Rb of the hydrocarbon solvent satisfies 1.5 < Rb < = 3; the ratio of the molar concentration Rc of LiPF6 to the molar concentration Rd of LiTFSI is more than 0 and less than or equal to 1. The composite electrolyte provided by the invention has excellent comprehensive physical and chemical properties, especially low-temperature performance, and can improve the cycle performance and rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite electrolyte, a lithium metal battery and applications thereof. Background Art

[0002] Energy shortages and environmental pollution force humans to develop sustainable and environmentally friendly clean energy. However, in order to break through the limitations of space and time and achieve efficient storage and conversion of new clean energy, it is necessary to further develop new and efficient energy storage devices. Traditional lithium-ion batteries based on deintercalation positive / negative electrode materials are close to the limit of energy density (300Wh / kg), and it is still difficult to meet the rapidly developing market demand for high-performance energy storage batteries. Therefore, the development and utilization of new electrode materials with high specific capacity to achieve higher energy density lithium-ion batteries is crucial to the future development of the energy storage field. The lithium metal negative electrode has an ultra-high theoretical specific capacity and a low electrode potential. Replacing the graphite negative electrode material will greatly increase the energy density of the lithium battery, so it has become one of the most concerned systems in the future lithium battery negative electrode.

[0003] The advantages of lithium metal anodes are ultra-high theoretical specific capacity (3860mAh / g, 2046mAh / L), ultra-low electrochemical redox potential (-3.04V vs. SHE), and low density (0.534g / cm). In addition to matching with traditional intercalation cathode materials, lithium metal anodes can also match with conversion-type lithium-free cathode materials, such as organic electrode materials and sulfur cathodes, which is expected to further improve the energy density of rechargeable batteries. However, metallic lithium has high reactivity and low redox potential, which inevitably causes most electrolytes to undergo side reactions on the negative electrode surface, forming an undesirable SEI, resulting in continuous consumption of lithium and electrolyte, seriously affecting the efficiency and cycle life of lithium metal batteries. Ether solvents have lower polarity and reduction potential than ester solvents, and are therefore often used as electrolyte solvents for lithium metal batteries. However, most ether electrolytes have both low reduction potential and low oxidation potential, and cannot simultaneously achieve high reduction resistance and oxidation resistance, resulting in poor compatibility between the lithium metal negative electrode and the high-voltage positive electrode, limiting the high energy density of lithium metal batteries. In addition, the lithium metal negative electrode is very sensitive to temperature. Lower operating temperatures will cause a sharp increase in the desolvation energy barrier of lithium ions, intensify the growth of lithium dendrites, bring serious battery safety issues, and greatly limit the application of lithium metal batteries at extreme temperatures.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] An object of the present invention is to provide a composite electrolyte having excellent comprehensive physical and chemical properties and capable of improving the electrochemical performance of lithium metal batteries.

[0006] Another object of the present invention is to provide a lithium metal battery having excellent cycle performance, rate performance and safety performance.

[0007] In order to achieve the above object of the present invention, the following technical solutions are specifically adopted:

[0008] A composite electrolyte, comprising a fluorinated cyclic ether solvent, an alkane solvent, LiPF6 and LiTFSI; the number of carbon atoms Ra in the fluorinated cyclic ether solvent skeleton satisfies 3 ≤ Ra ≤ 6; the volume ratio A of the fluorinated cyclic ether solvent satisfies 50% ≤ A < 100%; the volume ratio B of the alkane solvent satisfies 0 < B ≤ 50%; the structural tortuosity Rb of the hydrocarbon solvent satisfies 1.5 < Rb ≤ 3; the ratio of the molar concentration Rc of LiPF6 to the molar concentration Rd of LiTFSI satisfies 0 < Rc / Rd ≤ 1.

[0009] In some embodiments, the number of carbon atoms Ra in the fluorinated cyclic ether skeleton satisfies 5 ≤ Ra ≤ 6; the volume ratio A of the fluorinated cyclic ether solvent satisfies 50 ≤ A ≤ 70.

[0010] In some embodiments, the fluorinated cyclic ether solvent includes at least one of ethylene oxide, propylene oxide, methylpropylene oxide, 2,3-epoxybutane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane and 1,4-dioxane having at least one fluorine atom substitution.

[0011] In some embodiments, the volume ratio B of the alkane solvent satisfies 30 < B ≤ 50; the structural tortuosity Rb of the hydrocarbon solvent satisfies 1.75 < Rb ≤ 2.

[0012] In some embodiments, the alkane solvent includes a straight-chain alkane or a cyclic alkane having more than 6 carbon atoms.

[0013] In some embodiments, the ratio of the molar concentration Rc of LiPF6 to the molar concentration Rd of LiTFSI satisfies 0.2 < Rc / Rd ≤ 1.

[0014] In some embodiments, the cycle performance Y of the lithium metal battery prepared from the composite electrolyte and the Ra, the A, the Rb, the B and the Rc / Rd satisfy the relational expression:

[0015] wherein, 0 < Y < 12.

[0016] A lithium metal battery, comprising the composite electrolyte described above.

[0017] In some embodiments, it further includes a negative electrode sheet and a positive electrode sheet; the negative electrode sheet includes a lithium metal sheet, and the positive electrode sheet includes a ternary positive electrode sheet.

[0018] An electrical device comprises the lithium metal battery.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The composite electrolyte of the present invention uses LiPF6 as an initiator to initiate the ring-opening polymerization reaction of the fluorinated cyclic ether. LiTFSI has high solubility and contains three trifluorosulfonyl imide groups. The steric hindrance effect of LiTFSI is used to dilute the cationic polymerization reaction of LiPF6. At the same time, a saturated alkane solvent is introduced. The saturated alkane solvent has an extremely low LUMO value and an extremely high HOMO value and hardly participates in any redox reaction inside the battery. The electrochemical stability and steric hindrance effect of the saturated alkane solvent are used to balance the polymerization depth of the cyclic ether, avoid the formation of a solid electrolyte that increases the interface resistance with lithium metal, and cause the fluorinated cyclic ether to undergo a micro-polymerization reaction. A SEI rich in inorganic LiF and highly elastic polyether organic matter is formed on the surface of the lithium metal negative electrode, thereby inhibiting the occurrence of side reactions and negative electrode expansion failure, and achieving ultra-high coulombic efficiency. rate of lithium metal batteries; at the same time, the high oxidation resistance of the alkane solvent makes the composite electrolyte have a wider redox potential window, improves the compatibility of the high-voltage positive electrode in the lithium metal battery, and fully exerts the advantage of the high energy density of the lithium negative electrode; in addition, the alkane solvent has a lower polarity and a higher steric hindrance, which weakens the solvation ability. In a low-temperature environment, the desolvation energy barrier of lithium ions is greatly reduced, and the low-temperature performance of the lithium metal battery is greatly improved. The volume proportion A of the fluorinated cyclic ether solvent, the number of carbon atoms Ra of the fluorinated cyclic ether solvent skeleton, the volume proportion B of the alkane solvent, the molar concentration Rc of LiPF6 and the molar concentration Rd of LiTFSI of the present invention all meet certain conditions, which can ensure the excellent comprehensive physical and chemical properties of the composite electrolyte and good low-temperature performance.

[0021] (2) The lithium metal battery of the present invention has excellent cycle performance, rate performance and safety performance. DETAILED DESCRIPTION

[0022] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0023] According to one aspect of the present invention, the present invention relates to a composite electrolyte, comprising a fluorinated cyclic ether solvent, an alkane solvent, LiPF6 and LiTFSI; the number of carbon atoms Ra in the backbone of the fluorinated cyclic ether solvent satisfies 3 ≤ Ra ≤ 6; the volume ratio A of the fluorinated cyclic ether solvent satisfies 50% ≤ A < 100%; the volume ratio B of the alkane solvent satisfies 0 < B ≤ 50%; the structural tortuosity Rb of the hydrocarbon solvent satisfies 1.5 < Rb ≤ 3; the ratio of the molar concentration Rc of LiPF6 to the molar concentration Rd of LiTFSI satisfies 0 < Rc / Rd ≤ 1.

[0024] In the composite electrolyte of the present invention, LiPF6 acts as an initiator to initiate the ring-opening polymerization reaction of the fluorinated cyclic ether. LiTFSI has high solubility and contains three trifluoromethanesulfonylimide groups. Its steric hindrance effect is used to dilute the cationic polymerization reaction of LiPF6. At the same time, a saturated alkane solvent is introduced. It has an extremely low LUMO value and an extremely high HOMO value and hardly participates in any redox reactions inside the battery. Its electrochemical stability and steric hindrance effect are used to balance the polymerization depth of the cyclic ether, avoiding the formation of a solid electrolyte and increasing the interfacial resistance with the lithium metal, enabling the fluorinated cyclic ether to undergo a micro-polymerization reaction, forming a SEI rich in inorganic LiF and highly elastic polyether organic matter on the surface of the lithium metal anode, thereby inhibiting the occurrence of side reactions and the failure of the anode due to swelling, and realizing a lithium metal battery with ultra-high Coulomb efficiency; at the same time, the high oxidation resistance of the alkane solvent gives the composite electrolyte a wider redox potential window, improving the compatibility of the high-voltage cathode in the lithium metal battery and fully exerting the advantage of the high energy density of the lithium negative electrode; in addition, the alkane solvent has low polarity and high steric hindrance, weakening the solvation ability. In a low-temperature environment, the desolvation energy barrier of lithium ions is greatly reduced, and the low-temperature performance of the lithium metal battery is greatly improved. The volume ratio A of the fluorinated cyclic ether solvent, the number of carbon atoms Ra in the backbone of the fluorinated cyclic ether solvent, the volume ratio B of the alkane solvent, and the ratio of the molar concentration Rc of LiPF6 to the molar concentration Rd of LiTFSI in the present invention all satisfy the above conditions, thereby ensuring the comprehensive performance of the composite electrolyte.

[0025] In some embodiments, the number of carbon atoms Ra in the fluorinated cyclic ether solvent backbone satisfies 3 ≤ Ra ≤ 6, such as 3, 4, 5, 6. The number of carbon atoms in the fluorinated cyclic ether solvent backbone of the present invention is appropriate, and the ring tension of the cyclic ether molecular structure is large, so it is easier to undergo ring-opening polymerization, and the polymerization reaction is more intense. In some embodiments, the volume fraction A of the fluorinated cyclic ether solvent satisfies 50% ≤ A < 100%, and the values of A are, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 90%, 95%, etc. The volume fraction A of the fluorinated cyclic ether solvent refers to the percentage of the volume of the fluorinated cyclic ether solvent in the total volume of the fluorinated cyclic ether solvent and the alkane solvent. If the volume fraction is too high, the polymerization reaction is too intense to form a solid electrolyte. If the volume fraction is too low, an effective SEI cannot be formed. In some embodiments, the number of carbon atoms Ra in the fluorinated cyclic ether backbone satisfies 5 ≤ Ra ≤ 6; the volume fraction A of the fluorinated cyclic ether solvent satisfies 50 ≤ A ≤ 70.

[0026] In some embodiments, the volume fraction B of the alkane solvent satisfies 0 < B ≤ 50%, such as 10%, 15%, 20%, 25%, 30%, 40%, 50%, etc. The volume fraction of the alkane solvent represents the percentage of the volume of the alkane solvent in the total volume of the fluorinated cyclic ether solvent and the alkane solvent. A suitable volume fraction of the alkane solvent is more conducive to coordinating the stability of the electrolyte and the polymerization reaction of the fluorinated cyclic ether. If the volume fraction of the alkane solvent is too high, the dissociation degree of the lithium salt is easily reduced. If the volume fraction is too low, the polymerization reaction of the fluorinated cyclic ether cannot be balanced, and a solid electrolyte is easily formed. In some embodiments, the structural tortuosity Rb of the alkane solvent satisfies 1.5 < Rb ≤ 3, such as 1.6, 1.8, 2, 2.1, 2.3, 2.5, 2.8, or 3, etc. The structural tortuosity refers to the ratio of the number of hydrogen atoms to the number of carbon atoms in the alkane structure. The larger the tortuosity, the simpler the straight-chain alkane, and the smaller the tortuosity, the more complex the cyclic alkane, which is closely related to the effect of balancing the cyclic ether polymerization. In some embodiments, the volume fraction B of the alkane solvent satisfies 30 < B ≤ 50; the structural tortuosity of the hydrocarbon solvent satisfies 1.75 < Rb ≤ 2.

[0027] In some embodiments, the ratio of the molar concentration Rc of LiPF6 to the molar concentration Rd of LiTFSI satisfies 0 < Rc / Rd ≤ 1, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1. LiPF6 acts as an initiator to induce the cationic polymerization reaction of the fluorinated cyclic ether. However, too high a concentration of it will cause the cyclic ether polymerization reaction to be intense and form a solid electrolyte. LiTFSI has high solubility, combines with low-polarity fluorinated cyclic ethers and alkane solvents, improves the ionic conductivity of the electrolyte, and can balance the cyclic ether polymerization reaction induced by LiPF6 at the same time. In some embodiments, the ratio of the molar concentration Rc of LiPF6 to the molar concentration Rd of LiTFSI satisfies 0.2 < Rc / Rd ≤ 1.

[0028] In some embodiments, the fluorinated cyclic ether solvent includes at least one of ethylene oxide, propylene oxide, methylpropylene oxide, 2,3-epoxybutane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, and 1,4-dioxane, which is substituted with at least one fluorine atom. The fluorinated cyclic ether solvent can be one or a combination of multiple ones, such as a combination of propylene oxide and methylpropylene oxide, a combination of 1,3-dioxolane and 1,4-dioxane, etc.

[0029] In some embodiments, the alkane solvent includes: a straight-chain alkane or a cyclic alkane with more than 6 carbon atoms. It includes a straight-chain alkane or a cycloalkane solvent substituted with a methyl or ethyl group.

[0030] In some embodiments, the cycle performance Y of the lithium battery prepared from the composite electrolyte satisfies the relational expression with Ra, A, Rb, B, and Rc / Rd:

[0031] Wherein, 0 < Y < 12, such as 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 9, 9.5, 10, 10.5, 11, or 11.5, etc.

[0032] The compatibility of the electrolyte with the lithium metal battery is ultimately characterized by the battery cycle life, and is closely related to the reactivity, polarity, composition, and ratio of the electrolyte. The higher the volume fraction A of the fluorinated cyclic ether solvent, the smaller the number of skeletal carbon atoms Ra, and the higher the proportion of the initiator LiPF6 (i.e., the larger the Rc / Rd value), the more intense the acetal polymerization reaction, which easily generates a solid gel electrolyte, increases the negative electrode interface impedance, and induces lithium dendrites; in order to achieve the balance of the micro-polymerization reaction, it is necessary to increase the volume fraction B of the alkane solvent and its molecular structure tortuosity Rb, and at the same time regulate the total amount and ratio of the double-salt system to achieve the controllability of the acetal polymerization reaction and achieve the micro-polymerization reaction.

[0033] According to another aspect of the present invention, the present invention also relates to a lithium metal battery including the composite electrolyte.

[0034] The lithium metal battery of the present invention has excellent cycle performance, rate performance, and safety performance, and has excellent electrochemical performance under low-temperature conditions.

[0035] In some embodiments, the lithium metal battery further includes a negative electrode sheet and a positive electrode sheet; the negative electrode sheet includes a lithium metal sheet, and the positive electrode sheet includes a ternary high-voltage positive electrode sheet.

[0036] According to another aspect of the present invention, the present invention also relates to an electrical device including the lithium metal battery. The electrical device of the present invention includes an electric vehicle and a portable device.

[0037] The following is further explained in conjunction with specific embodiments and comparative examples.

[0038] Example 1

[0039] A method for preparing an electrolyte comprises the following steps:

[0040] In an argon glove box, 1,3-dioxolane fluoride and n-hexane were mixed evenly at a volume ratio of 70:30, and then LiPF6 with a molar concentration of 1 mol / L was added. After complete dissolution, 1.5 mol / L LiTFSI was added.

[0041] A method for preparing a battery comprises the following steps:

[0042] (1) Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 (NCM811), conductive carbon black (SP), carbon nanotubes (CNTs) and polyvinylidene fluoride (PVDF) were mixed in a solvent N-methylpyrrolidone at a weight ratio of 96:1:0.5:2.5 and stirred evenly to obtain a positive electrode slurry. Aluminum foil was used as a positive electrode current collector, the positive electrode slurry was coated on the positive electrode current collector, and then baked at 120°C for 1h, followed by cold pressing, cutting and slitting to prepare a positive electrode sheet.

[0043] (2) Preparation of negative electrode sheet: A laboratory 16 mm lithium sheet was used as the negative electrode sheet.

[0044] (3) Battery assembly: Arrange and assemble the above-mentioned positive electrode sheet, separator, and negative electrode sheet in order, inject the above-mentioned electrolyte, and obtain a button battery.

[0045] Example 2

[0046] A method for preparing an electrolyte comprises the following steps:

[0047] In an argon glove box, 1,3-dioxane fluoride and n-hexane were mixed evenly in a volume ratio of 70:30, and then LiPF6 with a molar concentration of 1 mol / L was added. After complete dissolution, 1.5 mol / L LiTFSI was added.

[0048] The preparation method of the battery of this embodiment is the same as that of Example 1 except that the above-mentioned electrolyte in this embodiment is used.

[0049] Example 3

[0050] A method for preparing an electrolyte comprises the following steps:

[0051] In an argon glove box, fluorinated 1,3-dioxane and cyclohexane were mixed evenly in a volume ratio of 70:30, and then LiPF6 with a molar concentration of 1 mol / L was added. After complete dissolution, 1.5 mol / L LiTFSI was added.

[0052] The preparation method of the battery of this embodiment is the same as that of Example 1 except that the above-mentioned electrolyte in this embodiment is used.

[0053] Example 4

[0054] A method for preparing an electrolyte comprises the following steps:

[0055] In an argon glove box, fluorinated 1,3-dioxane and 1,3-dimethyl-cyclohexane were mixed evenly in a volume ratio of 70:30, and then LiPF6 with a molar concentration of 1 mol / L was added. After complete dissolution, 1.5 mol / L LiTFSI was added.

[0056] The preparation method of the battery of this embodiment is the same as that of Example 1 except that the above-mentioned electrolyte in this embodiment is used.

[0057] Example 5

[0058] A method for preparing an electrolyte comprises the following steps:

[0059] In an argon glove box, fluorinated 1,3-dioxane and cyclohexane were mixed evenly in a volume ratio of 60:40, and then LiPF6 with a molar concentration of 1 mol / L was added. After complete dissolution, 1.5 mol / L LiTFSI was added.

[0060] The preparation method of the battery of this embodiment is the same as that of Example 1 except that the above-mentioned electrolyte in this embodiment is used.

[0061] Example 6

[0062] A method for preparing an electrolyte comprises the following steps:

[0063] In an argon glove box, fluorinated 1,3-dioxane and cyclohexane were mixed evenly in a volume ratio of 50:50, and then LiPF6 with a molar concentration of 1 mol / L was added. After complete dissolution, 1.5 mol / L LiTFSI was added.

[0064] The preparation method of the battery of this embodiment is the same as that of Example 1 except that the above-mentioned electrolyte in this embodiment is used.

[0065] Example 7

[0066] A method for preparing an electrolyte comprises the following steps:

[0067] In an argon glove box, fluorinated 1,3-dioxane and cyclohexane were mixed evenly in a volume ratio of 60:40, and then LiPF6 with a molar concentration of 0.5 mol / L was added. After complete dissolution, 2 mol / L LiTFSI was added.

[0068] The preparation method of the battery of this embodiment is the same as that of Example 1 except that the above-mentioned electrolyte in this embodiment is used.

[0069] Example 8

[0070] A method for preparing an electrolyte comprises the following steps:

[0071] In an argon glove box, fluorinated 1,3-dioxane and cyclohexane were mixed evenly in a volume ratio of 60:40, and then LiPF6 with a molar concentration of 1.25 mol / L was added. After complete dissolution, 1.25 mol / L LiTFSI was added.

[0072] The preparation method of the battery of this embodiment is the same as that of Example 1 except that the above-mentioned electrolyte in this embodiment is used.

[0073] Comparative Example 1

[0074] A method for preparing an electrolyte comprises the following steps:

[0075] In an argon glove box, 1,3-dioxolane fluoride was added to lithium salt LiPF6 at a concentration of 1 mol / L.

[0076] Experimental example

[0077] 1. Test of physical and chemical properties of electrolyte at room temperature 25℃

[0078] The linear voltammetric curves of the electrolytes in the embodiments and comparative examples were tested using an electrochemical workstation (VMP300) to analyze the reduction decomposition potential of the electrolytes on the surface of lithium metal. The prepared electrolytes were sealed and left to stand at room temperature for 12 hours to observe the polymerization state of the electrolytes.

[0079] The test results of the physical and chemical properties of the electrolytes in the embodiments and comparative examples at room temperature of 25°C are shown in Table 1. Wherein, Ra represents: the number of carbon atoms in the skeleton of the fluorinated cyclic ether solvent; A represents: the volume percentage of the fluorinated cyclic ether solvent; B represents: the volume percentage of the alkane solvent; Ra represents: the structural tortuosity of the hydrocarbon solvent; Rc / Rd represents: the ratio of the molar concentration of LiPF6 to the molar concentration of LiTFSI;

[0080]

[0081] Table 1 Test results of physical and chemical properties of electrolyte at room temperature 25℃

[0082] Group A Ra B R Rc / Rd Y Degree of polymerization Oxidation potential Lithium copper efficiency Example 1 70% 5 30% 2.33 2 / 3 1.96 solid 4.3 72.50% Example 2 70% 6 30% 2.33 2 / 3 2.35 gel 4.3 84% Example 3 70% 6 30% 2 2 / 3 2.61 Viscosity 4.32 85.20% Example 4 70% 6 30% 1.75 2 / 3 2.85 Viscosity 4.37 87.70% Example 5 60% 6 40% 2 2 / 3 3.86 liquid 4.43 99.50% Example 6 50% 6 50% 2 2 / 3 5.40 Insoluble 4.5 70.20% Example 7 60% 6 40% 2 1 / 4 4.97 liquid 4.42 99.30% Example 8 60% 6 40% 2 1 3.27 liquid 4.44 99.40% Comparative Example 1 100% 6 / / / / solid 3.65 65.60%

[0083] 2. Battery cycle performance test

[0084] Li-Cu half-cell at 0.5 mA / cm 2 The current density is discharged to 1 mAh / cm 2 , and then charged to 1V to test the cycle efficiency. Under different test temperatures, the Li-NCM811 battery and the Li-Cu full battery were activated at a rate of 0.2C for five cycles, and the charge and discharge voltage was 1.8-4.3V. The capacity of the battery discharged to 1.8V after the cycle was obtained, the first discharge capacity of the battery was recorded, and the capacity retention rate and average coulombic efficiency were calculated.

[0085] The performance test results of the batteries of various embodiments and comparative examples are shown in Table 2.

[0086] Table 2 Battery performance test results

[0087]

[0088] From the above, it can be seen that in each embodiment of the present invention, when 3<Y<5, the performance of the lithium metal battery is optimal, the composite electrolyte realizes a micro-polymerization reaction, maintains a liquid phase, and completely dissociates the lithium salt, and an effective SEI can be formed at the negative electrode to achieve better lithium-copper efficiency, and the positive electrode has good oxidation resistance and good low-temperature performance.

[0089] Comparing Examples 1-8 and Comparative Example 1, the content of fluorinated cyclic ether solvent and alkane solvent has the greatest influence on the Y value, and thus is most critical to the performance. When the proportion of alkane solvent is too low, the cyclic ether polymerization reaction is violent, the electrolyte is easy to form a solid gel electrolyte, and the lithium metal interface is degraded; when the alkane solvent content is too high, the dissociation degree of the lithium salt is easily reduced.

[0090] Compared with Example 1-2, increasing the number of carbon atoms in the fluorinated cyclic ether skeleton can reduce the degree of polymerization and improve performance.

[0091] Compared with Examples 2-4, by increasing the tortuosity of the alkane solvent, reducing the Rb value, replacing the straight-chain alkane with a cycloalkane or increasing the branched chain, the degree of polymerization reaction is suppressed and the performance of the battery is gradually improved.

[0092] Compared with Example 5 and Examples 7-8, the influence of lithium salt concentration on the performance of the battery is relatively small.

[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite electrolyte, characterized in that: Including fluorinated cyclic ether solvents, alkane solvents, LiPF6 and LiTFSI; The number of carbon atoms in the skeleton of the fluorinated cyclic ether solvent, Ra, satisfies 3≤Ra≤6; The volume proportion A of the fluorinated cyclic ether solvent satisfies 50%≤A<100%; The volume proportion B of the alkane solvent satisfies 0 <B≤50%; The structural tortuosity Rb of the hydrocarbon solvent satisfies 1.5<Rb≤3; The ratio of the molar concentration Rc of the LiPF6 to the molar concentration Rd of the LiTFSI satisfies 0<Rc / Rd≤1.

2. The composite electrolyte according to claim 1, characterized in that The number of carbon atoms in the skeleton of the fluorinated cyclic ether, Ra, satisfies 5≤Ra≤6; The volume proportion A of the fluorinated cyclic ether solvent satisfies 50≤A≤70.

3. The composite electrolyte according to claim 1 or 2, characterized in that: The fluorinated cyclic ether solvent includes at least one of ethylene oxide, propylene oxide, methylpropylene oxide, 2,3-butylene oxide, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane and 1,4-dioxane substituted with at least one fluorine atom.

4. The composite electrolyte according to claim 1 or 2, characterized in that: The volume proportion B of the alkane solvent satisfies 30≤B≤50; The structural tortuosity Rb of the hydrocarbon solvent satisfies 1.75<Rb≤2.

5. The composite electrolyte according to claim 1, characterized in that: The alkane solvent includes: a straight-chain alkane or a cyclic alkane having a carbon number greater than 6.

6. The composite electrolyte according to claim 1, characterized in that: The ratio of the molar concentration Rc of the LiPF6 to the molar concentration Rd of the LiTFSI satisfies 0.2<Rc / Rd≤1.

7. The composite electrolyte according to claim 1, characterized in that: The cycle performance Y of the lithium metal battery prepared by the composite electrolyte satisfies the relationship between Ra, A, Rb, B and Rc / Rd: Among them, 0 <Y<12。 8. A lithium metal battery, characterized in that: The composite electrolyte comprises the composite electrolyte according to any one of claims 1 to 7.

9. The lithium metal battery according to claim 8, characterized in that It also includes a negative electrode sheet and a positive electrode sheet; the negative electrode sheet includes a lithium metal sheet, and the positive electrode sheet includes a ternary positive electrode sheet.

10. An electrical device, characterized in that: Including the lithium metal battery as described in claim 8 or 9.

Citation Information

Patent Citations

  • Electrolyte for lithium metal secondary battery

    CN115117453A

  • Mixed ether-based electrolyte for low-temperature lithium battery

    CN115275355A

  • Electrolyte solvent, lithium metal battery electrolyte and lithium metal battery

    CN117317378A

  • Electrolyte for high-voltage battery as well as preparation method and application of electrolyte

    CN117878412A

  • Electrolyte and lithium-sulfur battery

    CN118380656A

Cited By

  • Electrolyte precursor solution, electrolyte and preparation method and application thereof

    CN119431762A

  • Nonaqueous electrolyte power storage element, nonaqueous electrolyte, and method for producing nonaqueous electrolyte power storage element

    WO2026048484A1